1978
DOI: 10.2307/1938541
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Seed Scatterhoarding: Coevolution of Fox Squirrels and Black Walnuts

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Granivores are likely to store food in numerous, widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
247
5
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(270 citation statements)
references
References 16 publications
12
247
5
2
Order By: Relevance
“…Our results showed that the density of agouti-made caches declined with increasing cache distance, in agreement with the prediction of Clarkson et al (1986), but not Stapanian & Smith (1978), who predicted that density should not be affected by distance. Several earlier studies have reported a similar negative relationship (Cowie et al 1981;James & Verbeek 1985;Clarkson et al 1986;Jansen et al 2004).…”
Section: Correlates Of Cache Spacingsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results showed that the density of agouti-made caches declined with increasing cache distance, in agreement with the prediction of Clarkson et al (1986), but not Stapanian & Smith (1978), who predicted that density should not be affected by distance. Several earlier studies have reported a similar negative relationship (Cowie et al 1981;James & Verbeek 1985;Clarkson et al 1986;Jansen et al 2004).…”
Section: Correlates Of Cache Spacingsupporting
confidence: 92%
“…A key prediction of optimal cache spacing theory (OCST, Stapanian & Smith 1978;Clarkson et al 1986) is that cache spacing increases with food value. Our study is among the first (but see Hopewell et al 2008) to test this prediction in terms of economic value, that is, value-of-exchange, by comparing cache pilferage and cache spacing across a spatial gradient of ambient food availability, which we quantified as the number of seeds over relative agouti abundance (cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second hypothesis -the 'theft-prevention hypothesis' -was that defleshing reduces post-dispersal seed predation by lowering the likelihood that seed-eating mammals recover cached seeds. Odour enhances cache detection by rodents and other macrosmatic mammals (Murie 1977, Stapanian & Smith 1978, Vander Wall 1991, Vander Wall et al 2003, and decaying fruit flesh and other soft material has a stronger odour than the seeds themselves. Defleshing might reduce cues that other animals use to find caches, and increase the recovery advantage for the cache owner.…”
Section: Introductionmentioning
confidence: 99%